SOCIAL IMPACT OF THE DEVELOPMENT OF GREAT GENERAL SOEDIRMAN AIRPORT ON THE COMMUNITY OF KEMANGKON VILLAGE BUKATEJA SUB-DISTRICT - Tyas, Karunia Zuraidaning; Darmawan, Almas Rifqi; Pangestu, Retno; Suwali, Suwali (UNPERBA, 2024)
The existence of an airport serves as a crucial facility for a region. It can also be an economic and social opportunity for the surrounding community. The Great General Soedirman Airport construction project commenced in 2018 on the site that formerly served as a military airbase for the Indonesian Air Force. This development is anticipated to have significant effects on the community in Bukateja, Purbalingga Regency. The research conducted in a qualitative descriptive. Both primary and secondary data were utilized in this study. Primary data were obtained through interviews with respondents meeting the specified criteria. The research findings reveal both positive and negative impacts experienced by the community. Positive impacts are evident in the economic activities flourishing within the community of Bukateja Subdistrict. Conversely, negative impacts are observed in the social aspect, with communities experiencing cultural exchanges and an increase in residential density.